Reports and memoranda. Communication techniques for effective management. - C.R. Parsons (AOSIS, 1985)
In any organisational structure, either in private or public sectors, the lines and methods of communication need to be fully understood and utilised by everyone in the organisation if efficiency of the institution or service is to be obtained. Communication may be upward, downward or horisontal, and it is essential for cohesion and morale in the institution that there is accuracy and courtesy throughout each stage of com m u n ic a tio n . Breakdown in communication at any point in the process or at any level in the hierachy will affect the functioning and the reputation of the whole institution or service.